Web-Based Literacy Program to Foster Students' Motivation and Reading Literacy - Arifin, Joko; Wachid Bambang Suharto, Abdul (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
This research is motivated by the low motivation to read and the low literacy score of students of SMP Negeri 2 Kejobong. To foster students' motivation and reading literacy skills, the Web-Based Literacy Program is used. The objectives of this study are: (1) to describe the management of the Web-Based Literacy program, (2) to describe the results of students' reading motivation, and (3) to find out students' reading literacy skills. This research uses qualitative and quantitative approaches, while data collection techniques use techniques: interviews, observations, documentation, and questionnaires. After processing and analyzing data, it was concluded that: (1) The management used in the Web-Based Literacy Program is the following activities: a) planning including the formation of a school literacy team, budgeting for website creation, school web design, and socialization of web-based literacy programs, b) organizing involving teachers and employees who are distributed into several roles and responsibilities, c) implementing (actuating) literacy programs carried out from 07.10 – 07.30 every Wednesday and Saturday, and c) supervision (controlling) including observation activities of the implementation of activities, checking the documentation of the attendance list, and checking the results of student summaries, (2) The web-based literacy program succeeded in increasing the reading motivation of SMP Negeri 2 Kejobong students, with an average motivation of 3.97 (good category). A total of 5.74% of students had good motivation, 67.2% were categorized as good, and 27.5% were categorized as very good, and (3) students' reading literacy ability increased by 10.83 points, from 62.94 before the web-based literacy program to 73.77 after the program was implemented. The percentage of students who achieved the Minimum Literacy Completeness Criteria also increased from 66.70% to 93.33%, or an increase of 26.67%.